Brain activation induced by psychological stress in nonpsychotic siblings of patients with schizophrenia - Castro, Mariana Nair (2017)
There is compelling evidence that environmental factors together with a large predisposing genetic component contribute to the risk for schizophrenia. Among such factors, psychosocial stress has been considered of paramount importance prior to the onset of psychotic symptoms. In order to characterize the brain response to mental arithmetic stress in individuals genetically predisposed to schizophrenia, we employed 3T-fMRI in 13 nonpsychotic siblings of patients with schizophrenia and in 13 healthy individuals. After a period of 6 min of resting state acquisition, a block design was utilized, including three blocks of a 1-min control-task, 1-min stress-task and 1-min rest after task. Nonpsychotic siblings displayed several differences in brain activity as compared with healthy individuals, including failure to engage the right hippocampus and orbitofrontal cortex (OFC) during stress and shortly thereafter. In addition, in this group hippocampal function was associated with cognitive performance rather than perceived stress. Indeed perceived stress was in contrast associated with activation of bilateral OFC and insulae. The pattern of brain activation observed may represent the CNS correlate of previous observations on heightened sensitivity to psychosocial stress in persons at increased genetic risk for schizophrenia. Its potential usefulness as a marker of increased genetic predisposition to schizophrenia requires further investigation.